An assessment of PCB and PBDE contamination in two tropical dolphin species from the Southeastern Brazilian coast. Issue 2 (30th December 2015) - Lavandier, Ricardo; Arêas, Jennifer; Dias, Patrick S.; Taniguchi, Satie; Montone, Rosalinda; de Moura, Jailson Fulgencio; Quinete, Natalia; Siciliano, Salvatore; Moreira, Isabel
Abstract: PCBs and PBDEs were determined in two dolphin species, Sotalia guianensis and Steno bredanensis, from an upwelling system off the Central-northern coast of Rio de Janeiro, Brazil. PCB levels varied from 0.040 to 0.75 μg g − 1 lw in muscles and from 0.022 to 1.32 μg g − 1 lw in liver samples from S. guianensis . In S. bredanensis, values varied from 0.085 to 11.3 μg g − 1 lw in muscles and from 0.024 to 18.6 μg g − 1 lw in livers. PCB-138, -153 and -180 were the major PCB congeners detected in both species, while BDE-47 was the predominant PBDE congener found in both species. Higher concentrations in S. bredanensis were possibly related to the different feeding habits for both delphinid species. These results contribute to extend the database on organic contamination in cetaceans from the southern hemisphere, understanding their distribution and environmental fate in Southeastern Brazil. Highlights: PCBs and PBDEs were measured in two dolphin species. PCB and PBDE levels in S. guianensis were lower than in S. bredanensis . BDE-47 was observed as major PBDE congener in both species. PCB-138, -153 and -180 were the major congeners detected in both species. Results confirm the existence of a PCB contamination source in Brazil.